Design and validation for a remote attestation security protocol - WANG Dan; WEI Jin-feng; ZHOU Xiao-dong (Tongxin xuebao)
By analyzing current remote attestation model, an improved remote attestation model was provided and de-signed.In order to verify whether it conforms to security requirement, a formal analysis method CSP was used to analyze the protocol and model it with CSP method.Meanwhile, it was checked with FDR tool.A loophole of the protocol was found.For solving the problem, an improvement to the protocol was made.It has been verified that security properties can be guaranteed by the re-validate.This protocol can be used for the remote attestation in trust computing and it can ensure the secrecy, integrity, authentication and freshmen in the interoperation process of the protocol.